Synergy of Technology and Accounting for Generation Z in Supporting the Implementation of Asta Cita and Indonesia's Economic Growth 2025 - ISLAMIATI HIDAYAH, (Shafin: Sharia Finance and Accounting Journal, 2025)
The transformation of the Indonesian economy as planned in Asta Cita requires strengthening digital infrastructure as well as improving the quality of human resources. In this context, Generation Z—as a productive age group and digital native—has strategic potential to support the implementation of the digital economy and inclusive financing. However, this potential has not been fully actualized due to low accounting literacy and the lack of integration of the education system and policies that combine technology and financial governance. This study aims to analyze the synergy between the mastery of technology and accounting by Generation Z in strengthening the direction of national digital economic policy. Using a qualitative approach based on literature studies, the results of the study show that the integration of technology skills and accounting literacy is very important to realize a transparent, efficient, and participatory economic ecosystem. Curriculum reform, education policies, and cross- institutional collaboration are needed so that Generation Z can become key actors in making Asta Cita a success towards a digitally competitive and sustainable Indonesia.